PRIORITY TASKS OF TOURISM DEVELOPMENT IN RUSSIA - Pogrebova, Elena; Glinkina, Elena (Revista Inclusiones, 2020)
The modern market of tourism services is one of the leading and most dynamically developing sectors of the economy. In many countries, tourism plays a significant role in shaping the GDP, enhancing the foreign trade balance, creating additional jobs, and providing employment. Acting as a stabilizer of socioeconomic development, tourism is the locomotive of the development of transport, communications, construction, and agriculture, as well as the production of consumer goods and services. It has a high investment animated effect (10 rubles (9.5 US cents) of investments in the tourism sphere bring 60 rubles (95 US cents) of total revenue in other sectors of the economy).